Understanding the Role of Spiritual Leadership on Group Innovativeness: A Parallel Mediation Approach - Ghaedi, Azar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
In this dissertation, a theoretical and empirical intervening model was proposed and tested. The model investigated the both the direct and mediated effect of spiritual leadership on employees’ group innovativeness (GI) via workplace bullying (WPB) and tolerance to incivility (TTI) as mediating variables, under the lens of spiritual leadership theory, social exchange theory, and intrinsic motivation theory. Three hundred and sixty-eight full-time employees of four-star and five-star hotels in İzmir and Bodrum regions of Turkey were engaged in the survey. Data generated from this sample were analyzed using Structural equation modeling (SEM). The results show that spiritual leadership significantly predicted group innovativeness; workplace bullying and partially mediated this relationship. The findings of this thesis enrich spiritual leadership-workplace mistreatment-innovativeness nexus in hospitality management literature. Explicitly, the results implied that managers could draw on the tenets of love, hope, and vision of spiritual leadership theory in designing organizational goals and vision to foster meaningfulness climate that will deter the presence of bullying or incivility. Keywords: Spiritual leadership, Bullying, Tolerance to incivility, Group innovativeness, Turkey.

ÖZ: Bu çalışma, manevi liderlik teorisi, sosyal değişim teorisi ve içsel motivasyon teorisi temellerinde, manevi liderliğin çalışanların grup yenilikçiliği üzerindeki doğrudan ve aracılı (işyerinde zorbalık ve nezaketsizliğe tolerans) etkisini araştıran bir model önermektedir. Türkiye'nin İzmir ve Bodrum bölgelerindeki 368 4 ve 5 yıldızlı otellerin tam zamanlı çalışanlarından elde edilen verileri analiz etmek için yapısal eşitlik modeli kullanılmıştır. Sonuçlar, manevi liderliğin grup yenilikçiliğini anlamlı ölçüde tahmin ettiğini göstermektedir. İşyerinde zorbalık ve nezaketsizliğe tolerans bu ilişkiye kısmen aracılık etmiştir. Bu tezin bulguları, otelcilik yönetimi literatüründeki manevi liderlik-işyerinde kötü davranışlar-yenilikçilik bağına ilişkin bilgimizi zenginleştirmektedir. Özellikle, bulgular yöneticilerin zorbalık veya nezaketsizliğin varlığını caydıracak anlamlılık iklimini teşvik etmek için örgütsel hedefler ve vizyon tasarlamada manevi liderlik teorisinin sevgi, umut ve vizyon ilkelerinden yararlanabileceğini ortaya koymuştur. Anahtar kelimeler: Manevi liderlik, Zorbalık, Nezaketsizliğe tolerans, Grup yenilikçiliği, Türkiye.
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2020. Supervisor: Prof. Dr. Ali Öztüren.
Keywords: Tourism; Employee Motivation; Job satisfaction--Employee morale--Attitude (Psychology); Personnel Management; Work productivity--Leadership; Spiritual leadership; Bullying; Tolerance to incivility; Group innovativeness; Turkey